2003
DOI: 10.1016/s0266-7681(03)00174-8
|View full text |Cite
|
Sign up to set email alerts
|

A Homodigital Switch Flap to Restore Sensation to the Ulnar Border of the Thumb Tip

Abstract: Three cases of irrevocable loss of sensation on the ulnar side of the thumb tip are presented in which switch of the radial pulp of the thumb tip to the ulnar side restored sensibility to this critical area, providing a useful functional reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Other techniques can be used to provide sensibility distally. Switch flaps from the ulnar to the radial side of the index finger (Foucher et al, 1989;Littler, 1977;Schuind et al, 1985) and from the radial to the ulnar side of the thumb (Elliot et al, 2003) are useful in this respect to restore sensation vital for pinching.…”
Section: Treatment Of Small Painful Nerves In Continuity By Division and Relocationmentioning
confidence: 99%
“…Other techniques can be used to provide sensibility distally. Switch flaps from the ulnar to the radial side of the index finger (Foucher et al, 1989;Littler, 1977;Schuind et al, 1985) and from the radial to the ulnar side of the thumb (Elliot et al, 2003) are useful in this respect to restore sensation vital for pinching.…”
Section: Treatment Of Small Painful Nerves In Continuity By Division and Relocationmentioning
confidence: 99%
“…Many authors have reported their results with this type of flap. Elliot et al (2003) described the use of a switch flap to restore the ulnar side of the thumb tip in three patients, providing good functional results. Foucher et al (1989) reported their experience with the use of homodigital neurovascular island flap for the reconstruction of 64 cases of digital pulp loss.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical re-orientation occurred in only 1, but despite this the reconstructed switch flap was used as the "pinch" contact point rather than the more proximal thumb [ 53 ]. Littler in 1946 [ 54 ].…”
Section: Limitationsmentioning
confidence: 99%